2019
DOI: 10.1016/j.compeleceng.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A review of reinforcement learning for autonomous building energy management

Abstract: The area of building energy management has received a significant amount of interest in recent years. This area is concerned with combining advancements in sensor technologies, communications and advanced control algorithms to optimize energy utilization. Reinforcement learning is one of the most prominent machine learning algorithms used for control problems and has had many successful applications in the area of building energy management. This research gives a comprehensive review of the literature relating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(81 citation statements)
references
References 68 publications
0
62
0
Order By: Relevance
“…Additionally, because reinforcement learning is computationally demanding, how to better integrate the computation platforms with the building management system is also important for the application of RL in buildings. Mason and Grijalva (2019) [26] reviewed the application of reinforcement learning for building energy management, including HVAC, water heater, appliances, lighting, photovoltaics (PV), batteries and the electrical grid. It was found that RL can typically provide savings of about 10% for HVAC and about 20% for water heaters.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Additionally, because reinforcement learning is computationally demanding, how to better integrate the computation platforms with the building management system is also important for the application of RL in buildings. Mason and Grijalva (2019) [26] reviewed the application of reinforcement learning for building energy management, including HVAC, water heater, appliances, lighting, photovoltaics (PV), batteries and the electrical grid. It was found that RL can typically provide savings of about 10% for HVAC and about 20% for water heaters.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Although the above-mentioned works are effective, there are two major drawbacks in training a DRL agent. Firstly, it is impractical to let the DRL agent to explore the state space fully in a real building environment since unacceptably high cost may be incurred [35] [46] [47]. Secondly, it may take a long time for the DRL agent to learn an optimal policy if trained in a real-world environment [46] [47].…”
Section: Applications Of Drl In a Single Buildingmentioning
confidence: 99%
“…Qolomany et al (2019) [4] and Djenouri et al (2019) [5] reviewed how machine learning and big data could be applied to smart buildings. Vázquez-Canteli & Nagy (2019) [6] and Mason, K. & Grijalva (2019) [7] reviewed how reinforcement learning, a subdomain of machine learning, could be used to enhance building control. Saha et al (2019) [8] reviewed how data analytics could be used for occupancy sensing in buildings.…”
Section: Introductionmentioning
confidence: 99%